PELATIHAN SISTEM PENCATATAN PERSEDIAAN PERUSAHAAN DAGANG BAGI SISWA RUMAH BELAJAR MAHKOTA KASIH INSANI - Henny, Henny; Prasetya, Billy; Ervina, Clarrisa (Jurnal Serina Abdimas, 2023)
The merchandising company inventory recording system is one of the topics that is not understood by the students of the Rumah Belajar Mahkota Kasih Insani, so students need additional education on this topic to support the student learning process at school. Therefore, the leadership of the Rumah Belajar Mahkota Insani tries to fulfill the desire for additional education for its students by inviting external parties who are experts in the field of accounting to provide community service activities in order to increase students' insight into the inventory recording system of merchandising companies. This insight enhancement is carried out by means of training methods given to 5 (five) students with a background in studying at a Vocational High School. The material provided in this activity is the characteristics of trading companies and the inventory recording system of merchandising companies. The implementation of this community service activity is that students are given a pretest before training activities, material explanations, practice questions, post tests, and evaluation of training activities are carried out. Based on the results of the pretest and posttest, it showed an increase in results before and after being given explanations and exercises about the material for the inventory recording system of merchandising companies. While the results of the evaluation of community service activities that 80% strongly agree and 20% agree that the training is useful and want to take part in similar training in the future. The evaluation stated that the implementation of community service was beneficial in supporting student learning and providing broader insight into the inventory recording system for students. Sistem pencatatan persediaan perusahaan dagang merupakan salah satu topik yang kurang dimengerti oleh siswa Rumah Belajar Mahkota Kasih Insani, sehingga siswa membutuhkan pendidikan tambahan mengenai topik tersebut dalam mendukung proses belajar siswa di sekolah. Oleh karena itu pimpinan Rumah Belajar Mahkota Insani berusaha memenuhi keinginan tambahan pendidikan bagi siswanya dengan cara mengundang pihak eksternal yang pakar dibidang akuntansi untuk memberikan kegiatan pengabdian kepada masyarakat guna meningkatkan wawasan siswa tentang sistem pencatatan persediaan perusahaan dagang. Peningkatan wawasan ini dilakukan dengan metode pelatihan yang diberikan kepada 5 (lima) siswa dengan latar belakang sedang menempuh sekolah di Sekolah Menengah Kejuruan. Materi yang diberikan dalam kegiatan tersebut adalah karakteristik perusahaan dagang dan sistem pencatatan persediaan perusahaan dagang. Pelaksanaan dari kegiatan pengabdian kepada masyarakat ini adalah siswa diberikan pretest sebelum dilakukan kegiatan pelatihan, penjelasan materi, latihan soal, posttest, dan evaluasi kegiatan pelatihan. Berdasarkan hasil pretest dan posttest menunjukkan adanya peningkatan hasil sebelum dan setelah diberikan penjelasan dan latihan soal materi sistem pencatatan persediaan perusahaan dagang. Sedangkan hasil evaluasi kegiatan pengabdian kepada masyarakat bahwa sangat setuju 80% dan setuju 20% siswa menyatakan pelatihan tersebut bermanfaat dan ingin mengikuti pelatihan sejenis di kemudian hari. Evaluasi tersebut menyatakan bahwa pelaksanaan pengabdian kepada masyarakat bermanfaat dalam mendukung belajar siswa dan memberikan wawasan yang lebih luas mengenai sistem pencatatan persediaan bagi siswa.